A sex/gender perspective on interventions to promote children's and adolescents' overall physical activity: results from genEffects systematic review - Carolin Schulze; Yolanda Demetriou; Sandra Emmerling; Annegret Schlund; Susan P. Phillips; Lorri Puil; Stephanie E. Coen; Anne K. Reimers (BMC, 2020)
Abstract Background To evaluate the effects of interventions on children's and adolescents' overall physical activity (PA) for boys and girls separately and to appraise the extent to which the studies haven taken sex/gender into account. Methods Systematic review and semi-quantitative analysis. Eleven electronic databases were searched to identify all relevant randomized and non-randomized controlled trials. Studies had to report overall PA as the main outcome to be eligible for inclusion in the review. The main outcomes of the studies is a quantified measure of overall PA. Additionally, all studies had to report sex/gender disaggregated overall PA at baseline and/or follow up and/or explain how they dealt with sex/gender during outcome analysis (i.e., sex/gender adjusted analyses) and/or report that there were no differences in the outcome when looking at sex/gender. PRISMA guidelines were followed. Two authors independently screened studies for eligibility and assessed the risk of bias. Semi-quantitative analyses were conducted to evaluate intervention effects, taking into account the extent to which studies have considered sex/gender aspects. To evaluate sex/gender considerations in primary studies, a newly developed sex/gender checklist was used. The study was registered previously (registration number CRD42018109528). Results In total, 97 articles reporting 94 unique studies with 164 outcomes for overall PA were included in the present review. Average sample size was 829 participants, ranging from five to 9839. Participants' ages ranged from three to 19 years. Our review shows that overall 35% of PA outcomes had significant effects in increasing overall PA of children and adolescents. Not including single sex/gender studies, 105 out of 120 PA outcomes resulted in same intervention effects for boys and girls. The interventions reported to have similar effects on PA outcomes for boys and girls showed higher quality of reporting sex/gender aspects of measurement instruments, participant flow and intervention content and materials than PA outcomes with effects only in boys or only in girls. Overall, consideration of sex/gender aspects in intervention studies is low. Conclusions There is still a need to address sufficient consideration of sex/gender aspects in developing and implementing interventions in the context of PA.